Changes in the Blood Pressure, Heart Rate and Body Mass of Physically Active Men in Response to Thermal Stress - Robert Podstawski; Grzegorz Bielec; Krzysztof Borysławski; Zoltán Alföldi; Arkadiusz Marzec (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2022)
Background: Finnish sauna is presently the most popular type of thermal therapy in Europe. Saunas are widely available in aquaparks, SPA centers and hotels. In Scandinavian countries sauna is regarded not only as a form of treatment, but as a part of the national lifestyle. Objective: The aim of this study was to evaluate sauna-induced changes in systolic (SBP) and diastolic blood pressure (DBP), heart rate (HR) and body mass in healthy men. Methods: Thirty healthy men aged 20-49 years (mean age: 31.2±11.3 years) attended four 12-minute Finnish sauna sessions (temperature: 90°C, humidity: 14-16%) with 6-minute breaks in between sessions, including cold water immersion for 1 minute. The participants' physical activity (PA) levels were evaluated with an IPAQ questionnaire. Sauna bathers' body composition, BP and HR were measured before the first and after the fourth sauna session. Results: A significant (p < .001) decrease in SBP and DBP values was noted in response to sauna regardless of the bathers' body mass, age and PA levels. The average HR increased significantly in younger, slimmer and more physically active participants. Sauna treatment induced a significant decrease in body mass loss regardless of all independent variables. Conclusions: Repeated 12-minute Finnish sauna sessions have a beneficial influence on the cardiovascular system. Finnish sauna can be recommended for healthy men with average and high PA levels as a means of decreasing BP. Body mass loss, on the other hand, is related to the loss of body fluids as a result of sweating.